Pengaruh Literasi Keuangan Digital Terhadap Perkembangan Usaha : Studi Kasus Pada Umkm Di Praya Kabupaten Lombok Tengah - Ardiansyah, Lalu Yayan; ., Darusalam; Febriana, Widia (Income : Digital Business Journal, 2023)
The lack of financial literacy among micro-entrepreneurs causes them difficulties in accessing external financing. Even though the financial literacy of the people of NTB is above the national average, this is not accompanied by optimal financial management from MSMEs, especially the Central Lombok district. This study attempts to analyze the effect of financial literacy on MSME actors and assess the level of financial literacy of MSME actors in Central Lombok. The primary data collection method was carried out by online questionnaires and face to face with the respondents. Researchers used simple linear regression analysis to determine the magnitude of the influence of variables. Based on hypothesis testing using the t-test, there is an influence between financial literacy and business development. Based on the linearity test, there is a positive influence between digital financial literacy on business development. This influence means that the higher the level of financial literacy, the higher the business development. Based on the modeling, the coefficient of determination that influences financial literacy on business development is 77.5%, while the rest is influenced by other factors.